Inflammatory Myofibroblastic Tumors in Paranasal Sinus and Nasopharynx: A Clinical Retrospective Study of 13 Cases. (15th October 2018) - Zhu, Zhenzhen; Zha, Yang; Wang, Weiqing; Wang, Xiaowei; Gao, Yali; Lv, Wei
Abstract : Background. Inflammatory myofibroblastic tumor (IMT), as a mesenchymal tumor, is common in the lung and abdomen but rare in the paranasal sinus and nasopharynx. Objective. This study aimed to summarize the clinical characteristics of IMT in the paranasal sinus and nasopharynx and analyze the relationship between the treatment and the overall survival (OS). Method. The clinical features, treatment, and follow-up data of patients diagnosed with IMT of the paranasal sinus or nasopharynx from 2006 to 2017 were retrospectively analyzed, and the previous literature was reviewed. Results. IMT often presents as an ill-defined soft-tissue mass with bone destruction and invasion of surrounding structures. The treatment methods used in this study were different combinations of surgery, prednisone, radiotherapy, and chemotherapy or observation alone. Three of the 13 patients were lost and the follow-up time of the remaining 10 cases ranged from 2 to 87 months (median, 39 months). Two patients died of the disease; the other eight patients were stable. The 5-year survival rate was 72%. Among the four methods of treatment, only treatment with prednisone was significantly correlated with better OS ( P = 0.046). Conclusions. IMT is an intermediate tumor that often mimics malignancy. We are not sure if IMTs in the nasal cavity are more aggressive because of the biology or if the location and local therapy in the head region is more complicated. Radiologic findings help know the extent of the lesion. For unresectable nasal IMT, combined therapy with glucocorticoids, chemotherapy, and radiotherapy is sometimes a better choice. Glucocorticoids are especially recommended as a basic part of the integrated therapy. However, the standard treatment needs further research.